Development and validation of Muslim Moral Emotions Inventory (MMEI) - Rezki Perdani Sawai; Sidek Mohd Noah; Abdul Rashid Abdul Aziz; Joki Perdani Sawai; Roslee Ahmad (Human Resource Management Academic Research Society (HRMARS), 2021)
The increased number of criminal offenses statistics among adolescents in Malaysia is alarming. This is believed to be rooted from the reduce of moral emotions such as shame and guilt in themselves. Therefore, this study presents the results of an exploratory factor analysis of the Muslim Moral Emotions Inventory (MMEI), a self-report measure of moral emotions of shame and guilt to overcome this issue. This instrument was administered to a sample of Malaysian-Muslims youth (n = 640) to determine the factor structure and internal reliability of these scales. The analysis showed that 18 items factored around four factors of perceived Guilt subscales includes God consciousness, Care for Others, Fear of Punishment and Forgiveness. Another 18 items factored around five factors of perceived Shame subscales include Positive Speech, Sensitive Towards Others Judgment, Safeguarding Chastity, Guarding One’s View and Modest Self-presentation. The Shame scale accounted for 54.48% of\the variance, while the Guilt scale accounted for 56.10% of the variance. The results of showed that the factor structure of the two moral emotions scales of the MMEI was significantly measured with the current sample of Muslims youth. Cronbach alpha, split-half coefficients and item analysis verified the reliability of instrument. The significance of adaptive shame and guilt as a unique contributor to psychological well-being and applications for the MMEI in assessment and outcome research among youth are discussed.